(untitled) (Biological Sciences - PJSIR, 2010)
. In the investigation of caffeine and heavy metal contents in four branded and six unbranded tea samples collected from local markets of Lahore, Faisalabad and Peshawar, the amount of caffeine and heavy metals in all the branded tea samples were in agreement with the international standards. In unbranded tea samples, though the amount of caffeine was within standard limits but two of the samples collected from Peshawar had high concentrations of lead being, 13.69 and 15.78 mg/kg, consumption of which can lead to serious problems.